Impact of functional status and biomarkers on hospital costs and readmission rates in geriatric patients: An observational study with comprehensive geriatric assessment - Irene Simonetti; Stefano Landi; Chiara Leardini; Anna Giani; Arianna Bortolani; Francesco Fantin (PLoS ONE, 2025)
This study aimed to analyze the association between functional status, biomarkers, and hospitalization characteristics on costs and the probability of re-admission at 30 and 180 days in geriatric patients. It is used an observational design with both administrative data and additional clinical data not usually collected. Multivariate linear regression for hospitalization costs and multivariate logistic regressions for readmissions were used. Variables studied included the Barthel Index, Charlson index, albumin and blood pressure levels, previous hospitalizations, length of stay (LoS), and controls. Data from 953 patients aged over 65, admitted to the Geriatric ward between September 1st, 2018, and December 31st, 2019, were analyzed. The Charlson comorbidity index, number of comorbidities, and LoS were positively related to hospitalization costs. Previous hospitalizations and LoS were the main predictors of readmission. Systolic blood pressure was negatively associated with the odds of re-admission but showed no association with hospital costs. Higher functional status, as measured by the Barthel index, was linked to lower odds of unplanned hospitalization but was not statistically significant for costs. Functional status and biomarkers had moderate effects on costs and readmission odds. These findings can aid in early healthcare planning and resource management, providing valuable information for prioritizing patients and designing cost-effective care interventions.